The role of some modern teaching methods for physical activity in reducing aggressive behavior among people with special needs: A field study at the School for the Deaf and Mute in the state of M'Sila - Bendkfal, rachid (sports creativity, 2025)
Physical activity, in its modern sense, is considered one of the most important areas of contemporary life, encompassing various psychological, social, and educational aspects, extending even to political and economic dimensions. This makes it a rich field for research, with the educational field being one of the most crucial, as it focuses on the human element, the raw material of any renaissance. In this research, the focus is on the student, the man of tomorrow. However, for the student to achieve the desired goals, several elements are necessary, both material, represented by resources and capabilities, and human, primarily represented by the teacher and the student, who are the two main parties in the educational process. In all of the above, educational physical activity is compelled to contribute to the school environment, complementing other subjects. This is achieved by aligning with the student's innate nature, which is fundamentally play. However, this can only be accomplished through a modern teaching method that takes into account the specific characteristics of this stage. Many researchers have developed different methods to achieve the desired goals, including the scholar Moston, who is credited with developing a set of modern direct and indirect methods, which are the subject of our research. This scholar identified four basic channels for the method: the physical, the psychological, and the educational. Social, emotional, and intellectual channels—these channels vary in their order depending on the nature of each teaching method, being higher in one method and lower in another. While the method is fundamentally related to the educational situations within the lesson, Moston defined the specific characteristics of each method, specifying what can and cannot be applied. Although many studies have explored the role of physical activity in addressing behavioral problems in schools, including aggressive behavior, Moston's modern teaching methods have focused primarily on technical and physical aspects, particularly those related to learning various athletic skills in different activities. Psychological studies of these methods remain scarce. Hence, the idea arose to study these methods from a psychological perspective with students with special needs through adapted sports activities, specifically regarding reducing aggressive behavior in schools. This is fundamentally related to the student's psychological state. The specific needs of students with special needs necessitate identifying the most suitable method that allows them to achieve self-actualization and unleash their potential in the lesson. This requires the teacher to control these methods and understand their psychological role. Aggressive behavior, from the perspective of self-affirmation, is among the most pressing issues in this context. In our current time, the degree of this behavior varies according to the method used, which is affected by a set of variables. The structure of the method differs from one method to another. This research came to delve into the study of some of the modern teaching methods of Moston, from which we chose the command method, the reciprocal method, and the training method among people with special needs in special schools, in order to know the degree of aggressive behavior by applying the different previous methods.